Investigation of the healing effects of Afyon Province hot spring waters on experimentally-induced fatty liver in mice - Bülent Elitok; Ibrahim Kişlalioğlu; Yavuz Ulusoy; Bahadır Kilinç (Ветеринария сегодня)
Due the increasing number of alcoholic fatty liver disease cases in the world, the development of methods for treating this disease is an urgent task. According to different publications mineral water from hot springs has a beneficial effect on liver cells. In this regard, an investigation was performed with the aim to assess the effectiveness of hot spring water from the Süreyya I spring (Afyonkarahisar province) in treatment of fatty liver disease. 50 one-day-old albino mice with an average body weight of 29.6 g were selected for the experiment. The tests of liver tissue, biochemical and hematological blood tests, as well as blood gas tests performed at this stage, demonstrated deterioration in all parameters. To prove the effectiveness of using hot spring water in the treatment of alcoholic fatty liver disease, two groups of 25 mice each were formed. The animals of the control group were given tap water to drink, and were also bathed (daily) in it for one hour. The mice of the experimental group were given the hot spring water to drink and bathed in it for 15 minutes every day. Histological tests and blood tests were performed on day 1, 7, 14, and 21 of the experiment using five animals randomly selected from each group. On day 21 of the experiment, the animals of the experimental group demonstrated a significant (p < 0.05) decrease in the total number of leukocytes, neutrophils, monocytes, as well as in the levels of aspartate aminostatesferase, alanine aminopenesferase, gamma-glutamyltransferase, low-density lipoproteins, total cholesterol, triglycerides. There was also an increase in erythrocyte, hemoglobin, hematocrit, total protein, albumin and high density lipoprotein levels (p < 0.05). The results of histopathological analysis also demonstrated positive dynamics. At the same time, no pronounced positive dynamics was observed in animals of the control group. Moreover, microscopy of liver samples showed an ongoing process of tissue degeneration. The data obtained allow us to conclude that it is advisable to use the hot spring water for the treatment of alcoholic fatty liver disease.